Protective effect of Lactobacillus-containing probiotics on intestinal mucosa of rats experiencing traumatic hemorrhagic shock - Wang Lei (De Gruyter, 2021)
This study was conducted to assess whether Lactobacillus-containing probiotics could protect intestinal mucosa in rats during traumatic hemorrhagic shock and to determine its underlying mechanisms. Healthy male Sprague–Dawley rats (300 ± 20 g) were randomly divided into four groups. During the study, reverse transcription polymerase chain reaction, western blotting, and hematoxylin and eosin methods were used. There was a significant increase in the expression of toll-like receptor 4 (TLR4) in the rats that experienced traumatic hemorrhagic shock, along with increased mRNA of tumor necrosis factor-alpha (TNF-α) and interleukin (IL)-6. Pretreatment with Lactobacillus-containing probiotics reduced TLR4 expression, decreased phosphorylation (Ser536) and acetylation (Lys310) of p65, and decreased TNF-α and IL-6 mRNA. The probiotics combined acetate Ringer’s group showed a less severe pathological manifestation compared to the other experimental groups. Lactobacillus-containing probiotics inhibited nuclear factor-kappa B signaling via the downregulation of TLR4, resulting in inflammatory homeostasis, which might be the mechanism whereby Lactobacillus protects the intestinal mucosa from damage caused by the traumatic hemorrhagic shock.